2006
DOI: 10.1007/s00232-005-7012-x
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical and Pharmacological Characteristics of Native Two-Pore Domain TASK Channels in Rat Adrenal Glomerulosa Cells

Abstract: Multiple genes of the TASK subfamily of two-pore domain K(+) channels are reported to be expressed in rat glomerulosa cells. To determine which TASK isoforms contribute to native leak channels controlling resting membrane potential, patch-clamp studies were performed to identify biophysical and pharmacological characteristics of macroscopic and unitary K(+) currents diagnostic of recombinant TASK channel isoforms. Results indicate K(+) conductance (gK(+)) is mediated almost exclusively by a weakly voltage-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 55 publications
1
27
0
Order By: Relevance
“…The presence of Task3 in zona fasciculata in males might contribute to the compensation observed in male Task1 Ϫ/Ϫ mice, which recovered normal adrenal zonation of the aldosterone synthase and normal aldosterone production after puberty (15). In agreement with previous reports (6,22) and disagreement with a very recent report (17), our experiments on primary cultured adrenocortical cells showed that the K ϩ current carried by Task3 channels is a major determinant of the resting membrane potential. Surprisingly, expression of the aldosterone synthase remained restricted to the zona glomerulosa in Task3 Ϫ/Ϫ mice of both sexes and did not mimic the ectopic fasciculata expression found in Task1 Ϫ/Ϫ mice (15).…”
Section: Electrophysiology and Ca 2؉ Signaling In Task3-expressing Glsupporting
confidence: 80%
“…The presence of Task3 in zona fasciculata in males might contribute to the compensation observed in male Task1 Ϫ/Ϫ mice, which recovered normal adrenal zonation of the aldosterone synthase and normal aldosterone production after puberty (15). In agreement with previous reports (6,22) and disagreement with a very recent report (17), our experiments on primary cultured adrenocortical cells showed that the K ϩ current carried by Task3 channels is a major determinant of the resting membrane potential. Surprisingly, expression of the aldosterone synthase remained restricted to the zona glomerulosa in Task3 Ϫ/Ϫ mice of both sexes and did not mimic the ectopic fasciculata expression found in Task1 Ϫ/Ϫ mice (15).…”
Section: Electrophysiology and Ca 2؉ Signaling In Task3-expressing Glsupporting
confidence: 80%
“…Although macroscopic K currents recorded from rat, bovine, and human ZG cells have revealed the expression of multiple voltagedependent K conductances, the mRNA for TWIK-related acidsensitive K (TASK)-1 and TASK-3 subunits is particularly abundant (20)(21)(22)(23). TASK-1 (KCNK-3, K2P3.1) and TASK-3 (KCNK-9, K2P9.1) are two closely related family members of the KCNK family of two-pore domain/four-transmembrane (2P/ 4TMS) K channels that form background or ''leak'' K channels.…”
mentioning
confidence: 99%
“…These behaviors are illustrated in whole-cell patch clamp records of macroscopic K + current (I K ) from a rat adrenal glomerulosa cell (Fig. 2), a cell type in which a homogenous TASK-like channel population has been found to mediate plasma membrane I K [134]. The steady-state IV relationship can be approximated by the GHK current equation over only a limited range of membrane potentials in the presence of either physiological or elevated extracellular K + concentrations; at positive potentials I K exceeded GHK predictions and at very negative potentials I K fell below GHK predictions.…”
Section: Biophysical and Pharmacological Characteristicsmentioning
confidence: 99%
“…Voltage-dependent inhibition by extracellular Mg 2+ contributed to the deviations from GHK predictions shown in Fig. 2, particularly at negative membrane potentials [134]. Extracellular Mg 2+ appeared to act as a fast channel blocker [83], reducing open channel current without affecting mean open time or macroscopic current activation and deactivation kinetics, although effects on the local K + concentration at the mouth of the pore due to shielding of surface charges [83] has not been excluded.…”
Section: Biophysical and Pharmacological Characteristicsmentioning
confidence: 99%